Rational engineering of transcriptional riboswitches leads to enhanced metabolite levels in Bacillus subtilis - Boumezbeur, Ahmed-Hocine; Bruer, Marius; Stoecklin, Georg; Mack, Matthias (Metabolic engineering, 2020)
Many metabolic pathways in bacteria are regulated by metabolite sensing riboswitches that exert their control at the level of transcription employing a termination-antitermination mechanism. These riboswitches represent engineering targets to modulate expression of genes and operons relevant for the biotechnological production of commercially relevant compounds. We show that removal of the transcriptional riboswitches that control purine biosynthesis and riboflavin biosynthesis in Bacillus subtilis leads to auxotrophic strains. As an alternative, we report a rational approach for engineering transcriptional riboswitches independently from the availability of structural data. This approach consists in the identification and deletion of a key nucleotide sequence exclusively involved in transcription termination without affecting formation of other secondary and tertiary structures, which can be involved in other functions. To demonstrate the efficacy of our approach, we tested it with regard to deregulation of the purine and the riboflavin biosynthetic pathways in B. subtilis. Following validation of the engineered transcriptional riboswitches using specialized reporter strains, our approach was implemented into a B. subtilis wild-type strain employing CRISPR-Cas9 genome editing. The resulting purine and riboflavin production strains were characterized at the level of gene expression, metabolite synthesis and growth, and a substantial enhancement was measured at each level. Moreover, applying our approach to deregulate the purine pathway of an industrial riboflavin overproducing strain with impaired growth led to an increase in biomass by 53%, which resulted in an enhanced total production of riboflavin in the culture.